Estimation of the influence of fracture parameters uncertainty on the dynamics of technological development indicators of the Tournaisian-Famennian oil reservoir in Sukharev oil field - Aleksanr A. Kochnev; Nikita D. Kozyrev; Sergei N. Krivoshchekov (Записки Горного института, 2022)
Issues related to the influence of reservoir properties uncertainty on oil field development modelling are considered. To increase the reliability of geological-hydrodynamic mathematical model in the course of multivariate matching, the influence of reservoir properties uncertainty on the design technological parameters of development was estimated, and their mutual influence was determined. The optimal conditions for the development of the deposit were determined, and multivariate forecasts were made. The described approach of history matching and calculation of the forecast of technological development indicators allows to obtain a more reliable and a less subjective history match as well as to increase the reliability of long-term and short-term forecasts.